A novel projected shell model method for nuclear level density - Sun Yang; Wang Jiaqi; Dutta Saumi; Wang Long-Jun (EPJ Web of Conferences, 2025)
We introduce a shell model method for calculating nuclear level density (NLD) generally applicable for arbitrarily heavy deformed nuclei. The method is novel because of our use of physical guidance for the construction of its configuration space and the computational breakthrough with the Pfaffian algorithm. Taking a well deformed even-even 164 Dy nucleus as an example, we solve exactly the eigenvalue equation to obtain a large ensemble of eigenstates of angular momentum and parity. Our results indicate a potential need to revise some common understanding of the structural behavior in the pair-breaking region where the structure changes in NLD of the compound nuclei would be sensitive for cross-sections of neutron capture.